Digital Leadership and Dynamic Managerial Capabilities - M.T. Ali, Nirwan; W. Jabid, Abdullah; Hadady, Hartaty; Hadi Sirat, Abdul (IJBLE Scientific Publications Community Inc., 2023)
The purpose of this research is to examine the influence between digital leadership and dynamic managerial capabilities. This research itself was conducted in the City of Ternate. The population in this study are all business actors both online and offline in Ternate City. Determination of the sample in this study using purposive sampling with a judgment sampling approach with the condition that the respondent is intended to have the capacity as a business leader and the business has a net worth of more than 50 million rupiahs up to a maximum of 500 million rupiahs. Besides that, only businesses are traded online. This aims to measure leadership digitally and dynamically the ability of a leader, totaling 106 people. Testing the hypothesis in this study using simple linear regression. The results of hypothesis testing indicate that the hypothesis proposed in this study is supported. Next, recommendations for future research are discussed.